Hubungan keteraturan menjalankan sholat dan puasa Senin Kamis dengan agresivitas - Alif Mu'arifah; Sri Mulyani Martaniah (HUMANITAS: Indonesian Psychological Journal, 2004)
This research aim to know the correlations Sholat (prayer) and Monday-Thurday Fasting toward aggression. The subject of the research includes all student of pychology Departement of Ahmad Dahlan Univesity. The sample is taken using proportional random sampling technique. Data is collected through questionnaires and analyzed using regression analysis.The research findings show that there is negative correlation between the regularity in sholat and Monday-Thursday fasting toward aggressivenes with a level of significance 5%. The negative correlation bettwen doing sholat regularly and aggressiveness is -0,168, while the negative correlation between Monday-Thursday fasting and aggressiveness is -0,109. The effective contribution of variable X1 (Sholat /prayer) to Y (aggressiveness) is 3,823% and the contribution of variable X2 and Monday-Thursday Fasting to Y (agressiveness) is 1,986 %. It means the regularity in doing sholat and Monday-Thursday fasting altogether contribute 5,809 % torward aggressiveness. Sholat and Monday-Thursday fastimg together can be used to predict aggressivernes using the formulation Y = 145, 0938 -0, 21436 X1, -0, 17436 X2 -0.Â